Higher order language - Anderson, Stavroola A. (Crime & delinquency, 2022)
Research has implicated oral language deficits as risk factors for antisocial behavior. The aim of this study was to investigate the relationship between higher order language skills and youth offending through a risk, promotive and risk-based protective factor paradigm. In a sample of adolescent males (n = 130; 13 to 20 years; 62% youth offenders) skills in understanding ambiguity, making inferences, and understanding figurative language were demonstrated to have risk and promotive effects in association with youth offending. Figurative language also met criteria for having risk-based protective effects for youth at high offending risk due to poor nonverbal skills. Conceptualization of higher order language skills through this paradigm promotes a broader frame of reference for considering theoretical models and practical interventions.